Induction of resistance to chimeric antigen receptor T cell therapy by transduction of a single leukemic B cell. (October 2018) - Ruella, Marco; Xu, Jun; Barrett, David; Fraietta, Joseph; Reich, Tyler; Ambrose, David; Klichinsky, Michael; Shestova, Olga; Patel, Prachi; Kulikovskaya, Irina; Nazimuddin, Farzana; Bhoj, Vijay; et al.
Abstract We report a patient relapsing 9 months after CD19-targeted CAR T cell (CTL019) infusion with CD19– leukemia that aberrantly expressed the anti-CD19 CAR. The CAR gene was unintentionally introduced into a single leukemic B cell during T cell manufacturing, and its product bound in cis to the CD19 epitope on the surface of leukemic cells, masking it from recognition by and conferring resistance to CTL019. A CAR gene unintentionally introduced in a contaminating leukemia cell during the manufacturing of CAR T cells caused a patient to relapse after therapy.